The crisis of the European Union or the crisis of European integration? Causes and effects (Economic and Political Thought, 2015)
The crisis of the European Union or the crisis of European integration?This dilemma, seemingly contradictory, is the subject of the analysis in thisarticle. The author tries to prove the thesis that today we are facing a crisis ofthe EU, which entails a crisis of European integration. According to the author,even if the European Union broke up, nobody and nothing would be able tostop the process of European integration, at most it might be slowed down. Atthe same time, the author emphasizes here that 2014, and particularly dramaticevents in Ukraine, the Middle East and North Africa show that the ‘end of thehistory’, in which people believed after the fall of communism in Europe wasan illusion. Triumphalism and the hope for eternal peace have ended, and thebelief in the gradual but inevitable democratization of the following countriesand societies has been strongly undermined. Peace and security of Europe andthe world are today – according to the author – seriously threatened. Elevenyears after the great enlargement of the EU in 2004, its numerous shortcomingshave been revealed and its role and prestige in the international arena haveweakened. The author is trying to answer the questions why it happened andwhat should be done to prevent the EU from disintegration.